Pensamento computacional integrado à matemática: uma proposta de atividades de estudo para o 6º ano do ensino fundamental II - Machado, Jean Alex Custódio (2021)
This research was developed in the Graduate Program in Educational Network Technologies (PPGTER) of the Federal University of Santa Maria (UFSM), in the area of concentration of Educational Network Technologies for Innovation and Democratization of Education, in the Management research line Educational Network Technologies. Its main objective was to analyze an integration of computational thinking (PC) with the mathematics of the 6th year of Elementary School II, according to the competence - Digital Culture - of the National Common Curricular Base (BNCC), which defines the organic and progressive set of all essential learning in which students must develop in the stages and modalities of Basic Education. Still, that the student must have a mastery of the digital universe, being able to make qualified and ethical use of the various existing tools and to understand Computational Thinking and the impacts of technology on his life and on society. Specifically, we sought to: a) Develop study activities (unplugged and plugged) that involved the integration of computational thinking with mathematics for the 6th Year of Elementary School II (final product); b) analyze the data collected from the members of the expert panels (mathematics teachers and class supervisors / coordinators) regarding the study activities; and c) presentation of the results of the analysis of the collected data. It is a case study, of an applied nature and aims to be descriptive and exploratory, with characteristics of bibliographic research and data analysis with a quantitative and qualitative approach. It is used as a data collection instrument for the analysis of the participants of the expert panels, by completing questionnaires. The results of the study show that the study activities developed are in accordance with the objects of knowledge and skills provided for in the BNCC. Furthermore, it is feasible to apply study activities in the classroom and that these can contribute to a better understanding of the BNCC's knowledge objects.